Promoting Well-Being of Children at School: Parental Agency in the Context of Negotiating for Support - Koskela, Teija (Frontiers in Education, 2021)
This study describes how parents experience their role in enhancing their children’s well-being and what this reveals about parental agency in the context of collaborations between home and school. In Finland, schools are among the most important environments for delivering services to children. The goal of this study is to bring into focus the parents’ dispositions in multi-agency interactions based on parents’ experiences and to make sense of both their successes and the barriers they face. The Finnish education system aims to develop itself according to inclusive principles. However, the inclusive school culture is still a work in progress. Parents’ agency and positions in collaboration with school personnel are ambivalent, and there are several assets and barriers that affect their ability to participate fully in discussions about their children’s well-being at school. In this article, parents’ positions are connected to situations where they negotiate the process of collaborative planning of support for their children’s learning and well-being in the school environment. Their experiences are analyzed qualitatively via interviews and the concept of agency, a sociological concept that refers to the mutual relation between a culture or structure and human agents’ opportunities to interact within given contexts. The results reveal qualitative differences in parents’ experienced agency. Parental agency is connected to given opportunities, and the key role in making agency possible in the schools is given for the teachers. Behind everyday practices, there are deeper questions about parents’ positions and value in collaboration.